Gain-of-Function Mutations and Copy Number Increases of Notch2 in Diffuse Large B-Cell Lymphoma - Lee, Suk Young; Kumano, Keiki; Nakazaki, Kumi; Sanada, Masashi; Yamamoto, Go; Nannya, Yasuhito; Suzuki, Ritsuro; Ota, Satoshi; Ota, Yasunori; Izutsu, Koji; Sakata-Yanagimoto, Mamiko; Hangaishi, Akira; et al. (Blood, 2007)
[Background] Signaling through the Notch receptors, triggered by the binding of ligands expressed on neighboring cells, has a key role in determining cell fate in a variety of cell lineages, including lymphocytes. The physiologic roles of two of the four mammalian Notch genes, Notch1 and Notch2, have been clarified in mouse models. Notch1 is preferentially expressed in immature T cells and is essential for specification of early hematopoietic progenitors toward the T-cell fate and for early T-cell development in the thymus. In contrast, Notch2 is preferentially expressed in mature B cells and is required for the generation of a mature B-cell subset, known as splenic marginal zone B (MZB) cells. Deregulation of Notch1 function results in the development of T-cell acute lymphoblastic leukemia (T-ALL) in a number of mouse experimental models, and more importantly, more than 50% of childhood and 30% to 40% of adult human T-ALL cases carry Notch1 mutations that lead to deregulated activation of Notch signaling, indicating that accelerated Notch signaling contributes to the development of human neoplasms. [Results and Discussion] We screened Notch2 gene mutations at the heterodimerization and PEST domains in 109 B-cell lymphoma samples, and found mutations in 5 samples, all of which were diffuse large B-cell lymphomas (DLBCL; in DLBCL, 5 of 63 samples, ∼8%). These mutations lead to partial or complete deletion of the PEST domain, or a single amino acid substitution at the C-terminus of Notch2 protein. All five DLBCL cases with Notch2 mutations were uniformly immunohistochemically negative for CD10 and positive for BCL6 and MUM-1, whereas only 10 out of 24 Notch2 mutation-negative subjects showed this staining pattern. This observation might imply a link between Notch2 mutations and a fraction of non-germinal center B-cell-like DLBCL (non-GCB-DLBCL), according to the immunohistchemistry-based DLBCL subclassification. Interestingly, high-density oligonucleotide microarray analysis revealed that two of the five Notch2 mutation-carrying samples had an increased copy number of the mutated Notch2 allele, and in another sample of the five the total copy number of the Notch2 allele was increased. Furthermore, in the Notch activation-sensitive luciferase reporter assay in vitro, mutant Notch2 receptors showed increased activity compared with wild-type Notch2. These findings implicate Notch2 gain-of-function mutations in the pathogenesis of a subset of B-cell lymphomas, and suggest broader roles for Notch gene mutations in human cancers.